Studi Tingkat Pelayanan Angkutan Umum Bus Trans Koetaradja Trayek Keudah Darussalam Kota Banda Aceh - Fanesha N, Munna; Saleh, Sofyan M.; Sugiarto, Sugiarto (Journal of The Civil Engineering Student, 2025)
Keudah - Darussalam is one of the routes of public transportation served within city of Banda Aceh with the main destination of travel is Darussalam as an education center. This study aims to analyze the Trans Koetaradja bus' level of service as a public transportation on corridor I of Keudah-Darussalam so that whether it can be classified in good condition, medium, or unfavorable. The data were collected through dynamic surveys and static surveys. The indicator used in this analysis refers to the standard indicator of service issued by the Directorate General of Land Transportation. The result revealed total assessment of each parameter for Keudah - Darussalam corridor is equal to 23.00. This is classified in good criteria based on the standard used which is 18.00 to 24.00.